Deliberative Public Engagement with Science: An Empirical Investigation - PytlikZillig, Lisa M. (SpringerBriefs in Psychology, 2018)
experimental manipulations of deliberative engagement; nanotechnology public policy issues; education-oriented communications; experimental social science; science, technology and society; innovation policy; cognitive-affective engagement; polarization of public attitudes